Regional Risks to Agriculture in West Africa : Agricultural Risk Impacts, Management Measures, and Financing Mechanisms Through a Regional Lens - World Bank (Washington, DC, 2022)
Agriculture is an increasingly risky business in much of the world, including the West African region. The World Bank has developed an Agricultural Risk Management (ARM) framework that assesses risks in systemic production, markets, and enabling environments to understand their total sectoral impacts and to prioritize them. Prioritizing risks improves targeting of risk management measures so that scarce resources can be allocated where they have the most impact. It also helps identify how to align other agriculture, environment, and social protection policies to manage existing risks. These risks are usually identified and managed at national levels, and the three key types are production risks, market risks, and enabling environment risks. This report focuses on how West African countries can benefit from collaboration in managing agrifood system risks and on the resulting need to adapt a regional lens to the ARM framework. Since both crop-specific growing areas and the risks they face often span national borders, there are substantial advantages that can be gained by stronger collaboration. There is a need to build layered approaches to manage risk that combine risk-mitigating, risk-transfer, and risk-coping instruments. These risk management approaches are needed within countries, with regional approaches building on national efforts. This report provides a foundational analysis to begin identifying needed actions for West African countries and at regional levels.